Gene expression profile analysis to discover molecular signatures for early diagnosis and therapies of triple-negative breast cancer - Alam, Md Shahin; Sultana, Adiba; Wang, Guanghui; Haque Mollah, Md Nurul (Frontiers in Molecular Biosciences, 2022)
Triple-negative breast cancer (TNBC) is one of the most lethal subtypes of breast cancer (BC) and it accounts for approximately 10%–20% of all invasive BC diagnosed worldwide. The survival rate of TNBC in stages III and IV is very low and a large number of patients are diagnosed in these stages. Therefore, the purpose of this study was to identify TNBC-causing molecular signatures and anti-TNBC drug agents for early diagnosis and therapies. Five microarray datasets that contained 304 TNBC and 109 control samples were collected from the Gene Expression Omnibus (GEO) database and RNA-seq data with 116 tumor and and 124 normal samples were collected from TCGA database to identify differentially expressed genes (DEGs) between TNBC and control samples. A total of 64 DEGs were identified, of which 29 are upregulated and 35 are downregulated, by using the statistical LIMMA r-package. Among them, seven key genes (KGs) were commonly selected from microarray and RNA-seq data based on high degree of connectivity through PPI (protein–protein interaction) and module analysis. Out of these 7 KGs, 6 KGs (TOP2A,BIRC5,AURKB,ACTB,ASPM, and BUB1B) were upregulated and one (EGFR) was downregulated. We also investigated their differential expression patterns with different subtypes and progression stages of BC by the independent datasets of RNA-Seq profiles from UALCAN database, which indicated them as the potential biomarkers for early diagnosis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyzes with the proposed DEGs were performed by using the online Enrichr database to investigate the pathogenetic processes of TNBC highlighting KGs. Then we performed gene regulatory network analysis and identified three transcriptional (SOX2,E2F4 and KDM5B) and three post-transcriptional (hsa-mir-1-3p,hsa-mir-124-3p and hsa-mir-34a-5p) regulators of KGs. Finally, we proposed KGs-guided 5 repurposable drug molecules (Imatinib, Regorafenib, PAZOPANIB,TENIPOSIDE, and DEXRAZOXANE) for TNBC through network pharmacology and molecular docking analysis. These drug molecules also showed significant binding performance with some cancer related PTM-sites (phosphorylation, succinylation and ubiquitination) of top-ranked 4 key proteins (EGFR, AURKB, BIRC5, and TOP2A). Therefore, the findings of this computational study may play a vital role for early diagnosis and therapies against TNBC by wet-lab validation.